(untitled) (New York, NY., 2005)
How to Plan and Execute Strategy provides you with 24 practical steps for devising, implementing, and managing market-defining, growth-driving strategies. Encompassing every stage of the strategic process, this tactic-filled handbook tells you what you need to do to: Define your businesses * Understand your opportunities and threats * Set feasible goals and objectives * Create the strategies to achieve your objectives * Identify and set priorities * Write your business plan * Communicate the strategy and obtain commitment * Integrate across functions * Monitor results, evaluate, and react. Successful corporate strategy must be strong enough to meet the needs of the marketplace, yet flexible enough to quickly adapt when that marketplace changes. How to Plan and Execute Strategy outlines a field-proven framework you can follow to design and implement such a strategy and strengthen your organization's competitive advantage while ensuring buy-in and implementation by every worker, at every level.
Keywords: Strategic planning.,Business planning